Government regulation of small and medium-sized enterprises: economic impacts and development challenges ("Journal "U". Economy. Management. Finance.", 2025)
The article analyses the impact of government regulation on the development of small and medium‑sized enterprises (SMEs) in Russia. It examines the key support measures, their economic effects, and the outstanding challenges facing the sector. The study highlights the need to enhance the efficiency of regulatory instruments, improve the targeting of state support, and strengthen legal protection for businesses. The analysis demonstrates that while state interventions have contributed to the growth in the number of SMEs, persistent issues—including a limited contribution to GDP, uneven access to finance, and regulatory instability—require more targeted and sustainable policy measures.
Keywords: small and medium sized enterprises (SMEs); government regulation; economic impacts; legal challenges